2016
DOI: 10.1016/j.obhdp.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Mad and misleading: Incidental anger promotes deception

Abstract: Emotions influence ethical behavior. Across four studies, we demonstrate that incidental anger, anger triggered by an unrelated situation, promotes the use of deception. In Study 1, participants who felt incidental anger were more likely to deceive their counterpart than those who felt neutral emotion. In Study 2, we demonstrate that empathy mediates the relationship between anger and deception. In Study 3, we contrast anger with another negative-valence emotion, sadness. We find that participants who felt inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 84 publications
(119 reference statements)
1
18
0
1
Order By: Relevance
“…On the one hand, Motro's results nicely fit with studies showing that guilt induction reduces cheating when experiencing physical weights (Kouchaki et al, 2014 ) and that anger promotes deception by reducing empathy and enhancing self-interest (Yip and Schweitzer, 2016 ). Also developmental research shows that in 4- and 8-years old children, anger enhances immoral (aggressive) behavior, and that this increment is mitigated by children's ability to anticipate guilt (Colasante et al, 2016 ).…”
supporting
confidence: 69%
“…On the one hand, Motro's results nicely fit with studies showing that guilt induction reduces cheating when experiencing physical weights (Kouchaki et al, 2014 ) and that anger promotes deception by reducing empathy and enhancing self-interest (Yip and Schweitzer, 2016 ). Also developmental research shows that in 4- and 8-years old children, anger enhances immoral (aggressive) behavior, and that this increment is mitigated by children's ability to anticipate guilt (Colasante et al, 2016 ).…”
supporting
confidence: 69%
“…Many factors influencing the propensity to lie have been identified, not only self-interest. These include emotion (Yip & Schweitzer, 2016), conflicting role demands (Grover & Chun, 1994), the type of information being falsified (Fulmer, Barry & Long, 2009), the psychological cost of lying (Shalvi, Handgraaf & De Dreu, 2011), and the level of cognitive development (Chung & Hsu, 2017).…”
Section: Lies Deceit and Organizationsmentioning
confidence: 99%
“…Many factors influencing the propensity to lie have been identified, not only self-interest. These include emotion (Yip and Schweitzer, 2016), conflicting role demands (Grover and Hui, 1994), the type of information being falsified (Fulmer et al, 2009), the psychological cost of lying (Shalvi et al, 2011b) and the level of cognitive development (Chung and Hsu, 2017). Attitudes toward workplace deception have also been shown to be affected by perceptions of organizational fairness and equity (Gino and Pierce, 2010;Greenberg and Bies, 1992), power (Koning et al, 2011;Olekalns et al, 2014a), levels of rapport (Jap et al, 2011), social distance (Ackert et al, 2011), the degree of rivalry and beliefs about competition (Kilduff et al, 2016;Roulin and Krings, 2016), pro-socialibility (Levine and Schweitzer, 2015;Steinel et al, 2010) and perceptions of trust and integrity (Haselhuhn et al, 2017;Olekalns et al, 2014b).…”
Section: Lies Deceit and Organizationsmentioning
confidence: 99%
“…In a recent article, Yip and Schweitzer () found that anger increases the use of deception in negotiations. In particular, they found that people who experience anger are more likely to use deception in a negotiation than people who experience neutral emotion or sadness.…”
Section: Empirical Findings On Emotions and Deceptionmentioning
confidence: 99%
“…In a recent study, Yip and Schweitzer () found that people who experience sadness are less likely to use deception in negotiations than people who experience anger. Sadness is a negatively valenced emotion that is associated with the appraisal of situational control (Smith & Ellsworth, ).…”
Section: Empirical Findings On Emotions and Deceptionmentioning
confidence: 99%